Collaborating With Sonographers and Vascular Technologists to Develop Ergonomics Interventions to Address Work-Related Musculoskeletal Disorders. (January 2019) - Sommerich, Carolyn M.; Evans, Kevin D.; Lavender, Steven A.; Sanders, Elizabeth; Joines, Sharon; Lamar, Sabrina; Radin Umar, Radin Zaid; Yen, Wei-Ting; Park, SangHyun
For more than two decades, surveys of imaging technologists have consistently reported high prevalence of work-related musculoskeletal discomfort (WRMSD). Yet, workplace intervention research involving sonographers is limited. In this study, a transdisciplinary team of researchers used a participatory approach to work with diagnostic medical sonographers (DMS) and vascular technologists (VT) to identify needs and opportunities for developing new approaches to work that will reduce sonographers' exposures to WRMSD risk factors. In this paper, we describe the approach and the resulting identified needs. We also describe the prototyping and testing of two work approaches that target specific needs of DMS and VT, respectively. We would like designers, manufacturers, engineers, and ergonomists, in collaboration with sonographers and their managers, to recognize this area of opportunity and come together to apply their knowledge of biomechanics and design in developing useful and usable workplace interventions (solutions) to reduce sonographers' WRMSD risk factor exposure.